Malignant ameloblastoma: a challenging diagnosis (2018)
Ameloblastoma is an uncommon and locally aggressive, benign, odontogenic tumor, with local recurrence when not adequately excised. A rare variant of this neoplasm with the benign features but accompanied with metastases has been described. This rare variant is malignant ameloblastoma and is known to have a poor prognosis. We present the case of a young woman who had recurrent mandibular tumors, which were resected twice and histologically reported as ameloblastoma. Four years later, she presented with pulmonary metastasis and atelectasis. A review of the literature on this very rare neoplasm was also performed.